Criminal Liability For Perpetrators of Concert Ticket Fraud via Social Media (Twitter) - Jeni Alindawati; Horadin Saragih (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
The development of social media as a means of interaction and economic transactions has also increased the risk of crime in the digital space, one of which is concert ticket fraud. The purpose of this study is to analyze the criminal liability for perpetrators of concert ticket fraud committed through social media platform X (Twitter), along with legal protection efforts for victims. This study is a normative juridical study, which is carried out through a statutory and conceptual approach. The legal materials used as references include primary, secondary, and tertiary legal materials obtained through literature studies and analyzed descriptively and analytically. The results of the study explain that the perpetrator's actions fulfill the elements of the crime of fraud as regulated in Article 378 of the Criminal Code and the elements of disseminating false and misleading information that causes consumer losses in electronic transactions, as stipulated in Article 28 paragraph (1) in conjunction with Article 45A paragraph (1) of the ITE Law. Legal protection for victims can be provided in the form of preventive and repressive protection. Repressive protection is realized through a criminal reporting mechanism and a lawsuit for compensation based on Article 38 paragraph (1) of the ITE Law, Article 1365 of the Criminal Code and the UUPK. The study concludes that the existing legal framework provides sufficient basis for law enforcement and the restoration of victims' rights, but further legal awareness and oversight of digital transactions are needed to prevent similar cases from recurring.